A rare cause of persisting anaemia in a patient with a failing Fontan circulation. (20th September 2016) - Lambrecht, Loes; Cools, Bjorn; Witters, Peter
Abstract: This case report describes intestinal angiodysplasias as a cause of persisting anaemia in a 16-year-old girl with a failing Fontan circulation. Although this is a very rare cause of anaemia, we highlight the importance of video capsule endoscopy in such patients to initiate a life-saving treatment.